THE EFFECT OF SUPPLEMENTATION OF CAPSULE WITH A COMBINATION OF MOMORDICA CHARANTIA FRUIT AND MORINGA OLEIFERA LEAVES EXTRACT ON THE BIOMARKER OF LIVER AND RENAL FUNCTION IN THE LIMITED HEALTHY VOLUNTEERS - ROSYID, FAHRUN NUR; HARYOTO; KRISTINAWATI, BETI; RAHMAN, AHMAD FADHLUR (International Journal of Applied Pharmaceutics, 2024)
Objective: This study examined the supplementation of the capsule with a combination of Momordica Charantia Fruit (MCF) and Moringa Oleifera Leaves (MOL) extract on the biomarkers of liver and renal function in limited healthy volunteers. Methods: This study used a nonrandom test. 78 healthy volunteers were given 2 x 1000 g of the capsules of MCF and MOL extract. This intervention was conducted for 30 d. The levels of GOT/AST, GPT/ALT, alkaline phosphatase, gamma glutamyl transpeptidase, urea, and creatinine were measured at baseline and at the end of treatment. Data were analyzed using paired t-test and Wilcoxon sign test with a significant limit of P ≤ 0.05. Results: This study showed a significant decrease in GOT/AST (P = 0.001), GPT/ALT (P = 0.001), Alkaline phosphatase (P = 0.007), gamma glutamyl transpeptidase (P = 0.002), urea (P = 0.009) and creatinine (P = 0.002). Conclusion: These findings indicated that supplementation of the capsule with a combination of MCF and MOL extract had a positive impact on liver and renal function biomarkers in limited healthy volunteers. This study contributes towards the extension of understanding the potential health benefits of supplementation of the capsule with the combination of MCF and MOL extract.